The regulation of conflicts of interests and the good government in Peru - Morón Urbina, Juan Carlos (2014)
This paper discusses the problem related to conflicts of interestand its various manifestations, particularly in public administration. in this regard, the author makes an ethical analysis of the concept, and he examines the regulation of conflicts of interest in the administrative field and its configuration as a constitutional limitation of fundamental rights. In this way, the paper concludes that the regulation of conflicts of interest in governance should aim to seek efficiency and balance since the position of a public servant implicates acting according to what is of general interest.